Adolescents and Teachers as Partners in a School-Based Research Project to Increase Physical Activity Opportunities in a Rural Community - Rye, James; Tompkins, Nancy O'Hara; McClure, Darlene; Aleshire, Jacqueline (The Rural educator (Fort Collins, Colo.), 2018)
Schools are an important resource in combating the physical inactivity and obesity epidemics in rural economically depressed areas. Through a University-community partnership, teachers and adolescents in a rural West Virginia county with one of the highest obesity rates in the state developed a school-based research intervention to increase physical activity opportunities. The intervention included walking routes, educational sessions, and pedometers. A survey about barriers to physical activity revealed that “lack of willpower” was a barrier of concern among program participants (mostly school employees) and had a statistically significant (p = .0033) pre to post mean score decrease during the year two offering. Focus groups with the adolescent researchers revealed that pedometers may facilitate maintenance of physical activity and a broader community impact. Focus group dialogue combined with teacher-researcher perspectives suggested that the adolescents changed their weight control paradigm from “dieting” to include the critical role of energy expenditure. Approval to conduct this research was provided by the West Virginia University Institutional Review Board for the Protection of Human Subjects Protocols No. 16041 and 15632. A poster based on this paper was presented at the 135th Annual Meeting & Exposition of the American Public Health Association, Washington, DC, November, 2007. The authors are very appreciative of the HSTA students for their continued efforts in addressing important public health problems in their community. The project described was supported by funds from the Centers for Disease Control and Prevention (CDC) Grant Award No. H75CCH322130-02 through the West Virginia University Prevention Research Center and by Grant Number 2R25RR12329-04 from the National Center for Research Resources (NCRR), a component of the National Institutes of Health (NIH). Its contents are solely the responsibility of the authors and do not necessarily represent the official views of CDC, NCRR, or NIH.